2003
DOI: 10.1152/ajpendo.00136.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucagon response to sympathetic nerve stimulation in the BB diabetic rat: effect of early sympathetic islet neuropathy

Abstract: Impaired glucagon response to sympathetic nerve stimulation in the BB diabetic rat: effect of early sympathetic islet neuropathy. Am J Physiol Endocrinol Metab 285: E1047-E1054, 2003. First published July 22, 2003 10.1152/ajpendo.00136. 2003.-We investigated the functional impact of a recently described islet-specific loss of sympathetic nerves that occurs soon after the autoimmune destruction of ␤-cells in the BB diabetic rat (35). We found that the portal venous (PV) glucagon response to sympathetic nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…The regulation of glucagon secretion during hypoglycemia is complex. There are data demonstrating that glucagon secretion during hypoglycemia is in part mediated via ANS mechanisms (31). However, there are also data in humans indicating that additional pathways exist for regulating the response of the hormone during hypoglycemia (18).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of glucagon secretion during hypoglycemia is complex. There are data demonstrating that glucagon secretion during hypoglycemia is in part mediated via ANS mechanisms (31). However, there are also data in humans indicating that additional pathways exist for regulating the response of the hormone during hypoglycemia (18).…”
Section: Discussionmentioning
confidence: 99%
“…was started, in diabetic mice only, 20 min into the stabilisation period to achieve baseline glucose levels similar to those of nondiabetic controls. A baseline blood sample was then drawn from the portal vein for later measurement of plasma glucose, glucagon and adrenaline concentrations, using assay methods described previously [18]. The volume of all portal vein blood samples was fully replaced by a concomitant jugular vein infusion of heparinised donor blood.…”
Section: Methodsmentioning
confidence: 99%
“…Sympathetic nerve fibres within the islet were identified by NPY immunostaining and quantified by tracing each fibre segment within an islet image using a computer (arrows in Fig. 2a) to obtain the cumulative area of NPY-positive nerve fibres (µm 2 /islet), as we have done previously for islet sympathetic nerves of BB and Wistar rats [17,18].…”
Section: Sympathetic Neural Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…While acknowledging that loss of the glucagon response to hypoglycemia in insulin-deficient diabetes cannot be attributed to classical diabetic autonomic neuropathy, Mei and colleagues (42,43) have suggested that it might be the result of an early sympathetic neuropathy that is limited to the pancreatic islets and unique to autoimmune diabetes. That suggestion is based on their finding of a reduced marker of sympathetic nerve terminals (vesicular monoamine transporter 2) in the islets of BB, but not streptozotocin-induced, diabetic rats (42) and reduced glucagon (46) and supported by data from studies of the perfused rat pancreas (47)(48)(49), rat islets (50), and rats in vivo (51), the intraislet insulin hypothesis posits that a decrease in ␤-cell insulin secretion, and thus a decrease in intraislet insulin and a decrease in tonic intraislet ␣-cell inhibition by insulin, is normally a signal for increased glucagon secretion in response to hypoglycemia.…”
Section: The Mechanism Of the Loss Of The Glucagon Response To Hypoglmentioning
confidence: 99%